Analisis Penerapan Green Building pada Gedung E, F, dan G di Institut Teknologi Kalimantan - Raftonado Situmorang; Hindiana Swastika; Tiara Rukmaya Dewi; Oryza Lhara Sari (Racic : Rab Construction Research, 2025)
Institut Teknologi Kalimantan (ITK) Campus  is currently planning a re-design that emphasizes the concept of Smart Eco-Campus and utilizing technological developments to create an environmentally environmentally friendly education. This program aims to increase the awareness and concern of the ITK campus community to contribute and be responsible for the environment. ITK campus to take part and be responsible for reducing global warming. global warming. Therefore, the research took a case study of on ITK campus buildings, precisely on buildings E, F, and G. This research refers to the application of the Green Building concept on the three buildings. refers to the application of the Green Building concept in the three buildings with the parameters of Greenship version 1.1 to the buildings that have been built with the purpose to find out how much the application of Green Building and get recommendations after getting validation from academics. recommendations after obtaining validation from academics and experts in the field of Green Building to further improve the application of Green Building. After assessment and validation, the points obtained for Building E amounted to 41 points with the Bronze predicate, in Building F points were obtained by 42 points with Bronze predicate and in Building G obtained points of 42 points with Bronze predicate. There are 4 categories of recommendations, namely the category of letter statement from top management, architectural category and policy and regulation category as well as recommendations for research support tools. and regulations and recommendations for research support tools